Teaching narrative theory - Herman, David; McHale, Brian; Phelan, James (New York : Modern Language Association of America, 2010)
The last two decades have seen a burst of renewed interest in narrative theory across many academic disciplines as scholars analyze the power of storytelling in print and other media. Teaching Narrative Theory provides a comprehensive resource for instructors who aim to help students identify and understand the distinctive features of narrativity in a text or discourse and make use of the terms and concepts of the field. This volume in the Options for Teaching series is organized to assist teachers at different levels of instruction and in different disciplinary settings. In twenty-one essays, the contributors discuss narrative theory's various teaching contexts (e.g., classes on literature, creative writing, and folklore and ethnography); key concepts and terms (e.g., story and plot, time and space, voice, perspective); applications beyond printed texts (e.g., film and digital media); and impact on other areas of theory (e.g., gender and ethnic studies). A glossary provides a guide to the challenging technical terminology characteristic of the field, and the volume as a whole emphasizes the importance of understanding and implementing technical terms in learning narrative theory.
Introduction / David Herman, Brian McHale, and James Phelan -- Part I: Situations. The undergraduate literature classroom / Suzanne Keen -- The undergraduate theory course / Robert F. Barsky -- The graduate classroom / Susan Mooney -- Across the curriculum: rhetoric and composition / Beth Boehm and Debra Journet -- Across the curriculum: creative writing / Brian Evenson -- Across the curriculum: folklore and ethnography / Amy Shuman -- Across the curriculum: history/historiography / Hans Kellner -- Across the curriculum: image-text studies / Emma Kafalenos -- Part II: Elements. Story, plot, and narrative progression / Brian Richardson -- Time, space, and narrative worlds / David Herman -- Voice; or, authors, narrators, and audiences / James Phelan -- Perspective / Jesse Matz -- Character and characterization / David Gorman -- Part III: Genres and media. Popular genres / Brian McHale -- Film / James Morrison -- Visual culture / Marianne Hirsch -- Digital media / Scott Rettberg and Jill Walker Rettberg -- Part IV: Interfaces. Gender / Robyn Warhol -- Ethnicity / Frederick Luis Aldama -- Ethics / Adam Zachary Newton -- Ideology and critique / Amy J. Elias -- Glossary.
Keywords: Narration (Rhetoric) -- Study and teaching; filmer; opetus; kerronta; narratologia; kirjallisuudentutkimus; narratiivinen tutkimus; media; retoriikka; luova kirjoittaminen; kirjallisuus; undervisning; berättande; narratologi; litteraturvetenskap; narrativ forskning; media; retorik; kreativt skrivande; litteratur